A new species of Ornithodoros (Acari: Argasidae) from desert areas of northern Chile - Muñoz-Leal, Sebastian (2016)
Ornithodoros atacamensis n. sp. is described from larvae collected on the lizard Liolaemus bisignatus and from free-living adults collected in desert areas from the Pan de Azúcar and Llanos de Challe National Parks, in Northern Chile. Additionally, unengorged larvae were obtained from fertilized females, which laid eggs in the laboratory. Morphological and mitochondrial 16S rDNA sequence analyses were performed in order to compare this new soft tick species with other congeneric Neotropical representatives. Larvae of O. atacamensis are morphologically closely related to Ornithodoros talaje sensu stricto, Ornithodoros puertoricensis, Ornithodoros rioplatensis, Ornithodoros guaporensis and Ornithodoros hasei, all belonging to the O. talaje species group. The larval diagnostic characters for this species are a combination of a large pyriform dorsal plate with a length of approximately 300 μm, 17 pairs of dorsal setae with five central pairs, hypostome with apex pointed and dental formula 2/2 in most rows, 3/3 apically, and capsule of the Haller’s organ oval in shape without reticulations. Phylogenetic analyses inferred from the mitochondrial 16S rRNA gene and a Principal Component Analysis based on morphometric characters provide additional support to the description of O. atacamensis as an independent lineage within the genus clustering within the O. talaje species group.